Transformational Leadership and Work Motivation as Determinants of Employee Performance: A Study of Manufacturing Companies in Medan - Mardaus Purba (Journal of Management, Economic, and Accounting, 2026)
In the highly competitive manufacturing industry, employee performance is clearly the primary foundation for achieving excellence. Transformational leadership, along with work motivation, have been shown to play a crucial role in enhancing this performance. This study specifically analyzes the influence of transformational leadership and work motivation, both separately and simultaneously, on employee performance at manufacturing companies in Medan. This study employed a quantitative approach through a survey method. Data were obtained by distributing questionnaires to 120 employees from various manufacturing companies in Medan, selected using purposive sampling. Data analysis involved multiple linear regression with the help of SPSS software version 25. The results of the analysis showed that transformational leadership had a positive and significant influence on employee performance (β = 0.305, p-value < 0.01). Meanwhile, work motivation had an even stronger and more significant influence (β = 0.498, p-value < 0.01). When tested simultaneously, both variables had a significant effect on performance (F-hit = 72.345, p-value < 0.01) with a coefficient of determination of 0.610, which means that 61% of the variation in employee performance can be explained by these two factors. It should be noted that work motivation emerged as the most dominant factor in its contribution. Based on these findings, it can be concluded that manufacturing companies in Medan should prioritize the development of transformational leadership within their management ranks, while simultaneously designing programs to increase work motivation, both intrinsic and extrinsic. Particular focus should be directed at the motivational aspect, given its significant influence on improving employee performance.